The role of technological change in income inequality in the United States - Deskoska, Elena; Vlčková, Jana; Žamberský, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This thesis examines the impact of the technological change on the income inequality in the United States of America. This is done by integrating theoretical and analytical findings about the channels through which technological change affects income inequality.The research is based on century-long income inequality data sets. However, it prioritizes the study of the income inequality in the years between 1970s and 2010s, as this period marks the kick off of the IT technologies and the globalization in the USA. Furthermore it includes an analysis of the role of globalization on the income inequality in the USA. It also accounts for the rest of the inequality triggers that are resulting from the political and economic structure of the country. Lastly it gives a prediction about the future state of the U.S. labor market and wages given the impact of the technologies of the Fourth Industrial Revolution.
Vedoucí práce: Jana Vlčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses